2022
DOI: 10.3389/fpsyg.2022.855063
|View full text |Cite
|
Sign up to set email alerts
|

Research on Bond Participants’ Emotion Reactions Toward the Internet News in China’s Bond Market

Abstract: The literature has widely studied the market response to the financial news or events but mainly focused on the stock market. This article associates the concept of internet news with the bond market response and attempts to examine how credit rating agencies (CRAs) and bond investors, two important bond participants, react to financial news on the internet with a range of multiply regressions. Our empirical study leads to several findings. First, CRAs tend to ignore the warnings of financial news on the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…As it is mentioned by Wu and Tian [6], empirical result of conducting the variables and empirical models has shown that among the three potential factors of the bond credit rating and the carbon risk which are the information transferred by the credit rating agencies, credit risk and the way of fund financed being invested, the result has shown that the information transferred by the credit rating agencies is less effective and inefficient in affecting the relationship between the bond credit spreads and the credit risk. The similar problem about the market efficiency of the bond market of China has also been mentioned by Hung et al [9] which is mainly caused by the "information asymmetry".…”
Section: Problemmentioning
confidence: 77%
See 3 more Smart Citations
“…As it is mentioned by Wu and Tian [6], empirical result of conducting the variables and empirical models has shown that among the three potential factors of the bond credit rating and the carbon risk which are the information transferred by the credit rating agencies, credit risk and the way of fund financed being invested, the result has shown that the information transferred by the credit rating agencies is less effective and inefficient in affecting the relationship between the bond credit spreads and the credit risk. The similar problem about the market efficiency of the bond market of China has also been mentioned by Hung et al [9] which is mainly caused by the "information asymmetry".…”
Section: Problemmentioning
confidence: 77%
“…The second problem is about the market efficiency of the bond market of China. As it is mentioned by Zhang, Wang and Tong [6], by using the econometric models to measure if the emotion behaviors of CRAs and bond investors are affected by the internet financial news, the result has shown that the internet financial news has almost no effect on the CRAs and both of the good or bad news are having strong effect on the emotion behavior of the bond investors. In this case, the situation and problems which has also been mentioned by Seafarer [5] has happened frequently where the crediting ratings of the bonds have only been decreased before serval days of default where the financial news about the default risk of the companies has long been mentioned in the internet financial news and has greatly affected the emotion behavior of the bond investors.…”
Section: Problemmentioning
confidence: 98%
See 2 more Smart Citations
“…This paper is subject to certain limitations that may present avenues for further research. Zhang et al (2022) find that in China’s bond market, investors’ reactions to good and bad news are asymmetric. In addition, the asymmetric effect of sentiment has been confirmed to exist in the stock market ( Akhtar et al, 2013 ).…”
Section: Conclusion and Discussionmentioning
confidence: 99%